Corrigendum to: ”Analisis Peran Na, K, Ca, dan Fe Terhadap Potensi Slagging dan Fouling pada Pembakaran Lignit, Sub-Bituminus, dan Ampas Tebu” - Dhafin Umara; Shofa Rijalul Haq; Rizki Khoiriah Nasution; Ratna Mustika Dewi; Muhammad Faiz Shafiyurrahman (Chemistry Department, 2026)
Slagging and fouling are major operational challenges in the combustion of coal and biomass, as they reduce thermal efficiency and accelerate equipment degradation. This study aims to analyze the role of sodium (Na), potassium (K), calcium (Ca), and iron (Fe) in influencing slagging and fouling tendencies in three fuels: sub-bituminous coal, lignite, and sugarcane bagasse. The data were obtained from proximate, ultimate, and XRF analyses, followed by the calculation of several predictive indices, namely the Base-to-Acid Ratio (B/A), Bed Agglomeration Index (BAI), Slag Viscosity Index (Sr), Fouling Index (Fu), Dolomite Ratio (Dol), and Simplified Base/Acid Ratio (B/As). The results indicate that Na and K play a dominant role in increasing fouling propensity, while Ca and Fe contribute to enhancing ash thermal stability. Sub-bituminous coal exhibits the most stable behavior with B/A = 0.49, Sr = 90.20, and Fu = 1.53, indicating low slagging and moderate fouling potential. Lignite shows the highest reactivity toward deposit formation with B/A = 8.77, BAI = 169.00, and Sr = 6.57, reflecting the dominance of basic oxides (Fe2O3 = 14.90%; CaO = 8.57%) and a low ash fusion temperature. In contrast, sugarcane bagasse demonstrates intermediate behavior with B/A = 0.58, Sr = 64.70, and Fu = 1.63, influenced by its very high SiO2 content (36.00%) and volatile alkalis such as K2O (2.47%). Overall, the findings show that increasing basic oxides (CaO, Fe2O3) reduces slagging tendency, whereas the dominance of alkali oxides (Na2O, K2O) enhances fouling potential.